Лексик компетенция ва коммуникатив компетенциянинг амалий ва назарий муаммолари тушунчасига доир фикр- мулохаза ҳамда таърифларнинг таҳлилий тузилиши - Ачилов Шохрухбек Шарибжон ўгли (International Scientific and Current Research Conferences, 2023)
This article talks about the importance of the formation, development and improvement of communicative competence in teaching foreign languages, practical and theoretical problems of communicative competence, some opinions on the concept of communicative competence in modern literature and the analytical structure of definitions.